IKLAN POLITIK ERA IMAGE DAN KEKUASAAN MEDIA - Riyanto, Bedjo (Nirmana, 2004)
The direct election of the president and vice president is succeed democratitation process. People has their own sovereignity to decide their own choice. Shifting mass mobilitation from political machine party to the power of mass media machine is the consequences of it. In the age of image recently%2C press and television broadcast have become a deciding factor of candidate winning. Who takes the power by force of this factor%2C is the winner. The victory of Susilo Bambang Yudhoyono and Jusuf Kalla to be president and vice president in general election September 20th 2004 is the evident of the thesis. Abstract in Bahasa Indonesia : political ad%2C the power of mass media%2C image building%2C candidate winning.